Maintenance of Self-Renewal and Pluripotency in J1 Mouse Embryonic Stem Cells through Regulating Transcription Factor and MicroRNA Expression Induced by PD0325901. (7th December 2015) - Ai, Zhiying; Shao, Jingjing; Shi, Xinglong; Yu, Mengying; Wu, Yongyan; Du, Juan; Zhang, Yong; Guo, Zekun
Abstract : Embryonic stem cells (ESCs) have the ability to grow indefinitely and retain their pluripotency in culture, and this self-renewal capacity is governed by several crucial molecular pathways controlled by specific regulatory genes and epigenetic modifications. It is reported that multiple epigenetic regulators, such as miRNA and pluripotency factors, can be tightly integrated into molecular pathways and cooperate to maintain self-renewal of ESCs. However, mouse ESCs in serum-containing medium seem to be heterogeneous due to the self-activating differentiation signal of MEK/ERK. Thus, to seek for the crucial miRNA and key regulatory genes that establish ESC properties in MEK/ERK pathway, we performed microarray analysis and small RNA deep-sequencing of J1 mESCs treated with or without PD0325901 (PD), a well-known inhibitor of MEK/ERK signal pathway, followed by verification of western blot analysis and quantitative real-time PCR verification; we found that PD regulated the transcript expressions related to self-renewal and differentiation and antagonized the action of retinoic acid- (RA-) induced differentiation. Moreover, PD can significantly modulate the expressions of multiple miRNAs that have crucial functions in ESC development. Overall, our results demonstrate that PD could enhance ESC self-renewal capacity both by key regulatory genes and ES cell-specific miRNA, which in turn influences ESC self-renewal and cellular differentiation.